Occurrence of the Elongated Styloid Process on Digital Panoramic Radiographs in the Riyadh Population - Lingam Amara Swapna; Nada Tarek AlMegbil; Alhanouf Othman Almutlaq; Pradeep Koppolu (Radiology Research and Practice)
Background. Patients with an elongated styloid process might present with dysphagia and pain in the cervicofacial region. These patients could be misdiagnosed as other orofacial pathologies. Aim. The present study attempted to assess the prevalence of the elongated styloid process on digital panoramic radiographs in the Riyadh population. Materials and Methods. The present prospective randomized study was conducted on the panoramic digital radiographs of 300 randomly selected patients visiting a private dental hospital to identify any elongation of the styloid process. Only the radiographs without any magnification errors were considered. The styloid process length was measured using the Sidexis measuring tool and entered in an Excel spreadsheet with other demographic data. A length beyond 30 mm was considered styloid process elongation. The data were subjected to statistical analysis. Results. The symptoms of styloid process elongation were higher among females (78.6%), and this difference was statistically significant (χ2 = 7.182; P=0.007). No statistically significant association was observed between styloid process elongation and symptoms between different age groups. Females exhibited a significant longer mean length of the styloid process than males. The present study exhibited a 27.3% prevalence for the elongation and calcification of the styloid process. Conclusion. Given the significant prevalence of the elongated styloid process in our study, we recommend it to be considered as one of the differential diagnosis for pain or discomfort in the orofacial region.